Reverse EDM process for pattern generation using powder metallurgical green compact tool. Issue 15 (17th November 2020) - Mazarbhuiya, Rashed Mustafa; Rahang, Maneswar
ABSTRACT: This work has described about the generation of complex shaped pattern using reverse electro discharge machining process. Powder metallurgical green compact tool has been used to generate a predefined pattern by depositing its constituent materials. A predefined star shaped pattern has been generated on the aluminum 6061 work surface. The pattern has been created by adjusting the process factors like compact load, current and pulse duration. The edge deviation and surface roughness have been considered as the performance measures in this experimentation. An optimum condition has been obtained at compact load of 20 tons, current of 1 A and pulse duration of 100 µs. Minimum surface roughness of 1.7 µm and minimum edge deviation of 13.07 µm have been achieved at this condition. The patterns are characterized by SEM, EDS and XRD analyses. The surface of the patterns is evaluated by a surface profilometer. The layer thickness is evaluated by an optical microscope. The microhardness of newly generated surface of pattern has been found to be of 329 Hv.